Pharmaceutical analysis :a textbook for pharmacy students and pharmaceutical chemists /David G. Watson, BSc, PhD, PGCE, with contributions by RuAngelie Edrada-Ebel, BSc, MSc, DrRerNat, AMRSC, Bhavik A. Patel, BSc, PhD, MRSC - Watson, David G.,1952-
Includes bibliographical references and index.